Микроэлементный статус крови при саркоидозе; Наука вчера, сегодня, завтра - Денисова О. А.; Егорова К. К.; Барановская Н. В. Наталья Владимировна; Рихванов Л. П. Леонид Петрович; Черногорюк Г. Е. (2013, 2013)
Заглавие с экрана